(NuKRA)QÇNSXKA LÆTERATURA (B10-11 (NKLASI (B((NPROFÆLXNIJ RÆWENX(B)s)E (2018)
(NpROGRAMA DLQ PROF)QÆLXNOGO NAW^ANNQ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmETODIKA NAW^ANNQ U SEREDN)QÆJ [KOLÆs)E -- (NPROGRAMIs -- (NUKRA)QÇNSXKA LÆTERATURAs)E -- (NuKRA)QÇNAs)E; (NSEREDNQ OSW)QÆTAs)E; (NZAGALXNOOSW)QÆTNÆ NAW^ALXNÆ ZAKLADIs)E; (NNAW^ALXN)QÆ PROGRAMIs)E; (NUKRA)QÇNSXKA LÆTERATURAs)E; (NPROF)QÆLXNE NAW^ANNQ Z UKRAÇNSXKOÇ LÆTERATURIs)E; (NF)QÆLOLOGÆ^NIJ PROFÆLXs)E